The Effectiveness of DPR Constitutional Rights in Overseeing the Executive Under Governing Coalition Dominance - Irmanjaya Thaher (Hakamain: Journal of Sharia and Law Studies, 2024)
This study examines the effectiveness of the constitutional rights of the Dewan Perwakilan Rakyat (DPR) in overseeing the executive under the dominance of the governing coalition in Indonesia's presidential system. Although the 1945 Constitution grants the DPR the rights of interpellation, inquiry, and expressing opinions as principal oversight instruments, their practical implementation is frequently influenced by coalition politics that weaken institutional accountability. This research employs a normative juridical method with statutory, conceptual, and case approaches. Primary legal materials consist of the 1945 Constitution, Law Number 17 of 2014 concerning the People's Consultative Assembly, the DPR, the Regional Representative Council, and the Regional House of Representatives, as amended, together with Constitutional Court decisions, parliamentary documents, and relevant scholarly literature. The findings demonstrate that the effectiveness of the DPR's constitutional rights is constrained by party discipline, coalition bargaining, executive dominance, and political interests that discourage the use of oversight mechanisms against the government. Consequently, constitutional oversight tends to function as a formal institutional procedure rather than an effective instrument of checks and balances. The study concludes that strengthening parliamentary independence requires reforms that reinforce institutional autonomy, improve transparency in oversight procedures, enhance the accountability of coalition politics, and ensure that constitutional rights are exercised consistently according to democratic principles and the rule of law. This study contributes to constitutional law scholarship by explaining how coalition dominance reshapes parliamentary oversight and offers a framework for reinforcing the effectiveness of legislative control within Indonesia's contemporary presidential democracy.